P-222 Breaking tradition in palliative care- introduction of remote technology and virtual consultations. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Roberts, Sarah; Parkes, Nicola; Salt, Susan; Huttley, Julie
Abstract : The aim of the project was to develop a strategic vision in three stages for the palliative care service to improve and expand our reach to patients that incorporated the use of technology. The project aimed to use virtual technology to open up access for consultant led advice in the patients home via video link consultation. This would allow more access to face to face consultations, a more responsive service, less travel time and more access to allow a "tech savvy" population to connect directly with the service. The second aim of the project was to allow the service to utilise technology to enhance sharing of knowledge and skills to our community colleagues, opening up access to web based educational "bitesize" programmes to improve and enhance skills of our community colleagues. The final aim of the project is to utilise technology to connect with our community partners to enhance communication and consultation with and about patients. We would use this with our out of hours providers as part of a community hub approach, using technology within the patients home to seek direct clinical advice enhanced by video links.